Учет стоимости жизни человека при расследовании сложных техногенных аварий горной промышленности - Кобылянский, Борис Борисович; Мнухин, Анатолий Григорьевич (НТУ "ХПИ", 2015)
В статье выделены и проанализированы различные подходы к оценке стоимости жизни человека, определены факторы, влияющие на оценку стоимости жизни человека при анализе тяжелых техногенных аварий в угольных шахтах. На основании данных Макеевского научно-исследовательского института о смертельном травматизме, был проведен численный анализ определения «стоимости жизни» на предприятиях угольной промышленности Украины.

The various approaches to assessing the valuation of human life are identified and analyzed, the factors affecting the valuation of human life in the analysis of serious technological accidents in coal mines are defined. On the basis of Makeyevka Research Institute of fatal injuries was conducted numerical analysis of valuation of "human life" in the coal industry of Ukraine. In turn, the analysis showed that the estimates of the living cost on the "method of determining the damage to the national economy from the injury (death) of people (the definition of the economic impact of the preserva-tion of life) most fully reflect all aspects of human activity, the circumstances of injury or death, causing the individual physical and mental suffering in connection with the transfer of the loss or injury.
The cost of living person in investigating complex man-made accidents the mining industry
Keywords: угольная промышленность; смертельный травматизм; компенсационные выплаты; оценка техногенного риска; valuation of human life; technogenic accidents; coal industry